2012
DOI: 10.1063/1.4767649
|View full text |Cite
|
Sign up to set email alerts
|

Charged electret deposition for the manipulation of high power microwave flashover delay times

Abstract: A quasi-permanent charged electret is embedded into the radiation window of a high power microwave system. It was experimentally observed that the additional electrostatic field introduced by the electret alters the delay times associated with the development of plasma at the window surface, resulting from high power microwave excitation. The magnitudes of both the statistical and formative delay times are investigated in detail for different pressures. Experimental observations are related to calculated disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The time necessary to amplify a background density of electrons n 0 to a critical density n crit (i.e. the formative time) can be approximated as τ f ∼ ln(n crit /n 0 )/ν iz where τ f and ν iz are the formative time and ionization rate, respectively [13]. For pulse widths exceeding the formative delay time, a collapse in the potential is observed, corresponding to the development of a high electron density and consequently low impedance discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The time necessary to amplify a background density of electrons n 0 to a critical density n crit (i.e. the formative time) can be approximated as τ f ∼ ln(n crit /n 0 )/ν iz where τ f and ν iz are the formative time and ionization rate, respectively [13]. For pulse widths exceeding the formative delay time, a collapse in the potential is observed, corresponding to the development of a high electron density and consequently low impedance discharge.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Methods to increase breakdown thresholds of dielectric windows are of great importance. [4][5][6][7][8][9][10][11] Periodically grooved dielectric windows have been found to increase the breakdown thresholds both for vacuum/dielectric 5,6 and air/dielectric 4 interfaces. External dc electric field is also suggested as an approach to suppress or initiate the dielectric window breakdown on vacuum 7 and air 8,9 sides.…”
mentioning
confidence: 98%
“…[4][5][6][7][8][9][10][11] Periodically grooved dielectric windows have been found to increase the breakdown thresholds both for vacuum/dielectric 5,6 and air/dielectric 4 interfaces. External dc electric field is also suggested as an approach to suppress or initiate the dielectric window breakdown on vacuum 7 and air 8,9 sides. Recently, Chang et al found that low-amplitude external magnetic field, with gyrofrequency X ¼ eB/m close to angular frequency x of rf electric field and with direction perpendicular to rf electric field and parallel to dielectric surface, can suppress effectively the multipactor effect on vacuum/dielectric interface.…”
mentioning
confidence: 98%